Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to